This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: y 00-6 y + 9 y = 0. When a constant coecient dierential equation leads to a repeated root, then multiply the exponential solution by t to get a second solution. EXAMPLE. Find the solution of 16 y 00 + 24 y + 9 y = 0 that satises the initial conditions y (0) = 1, y (0) = 3 / 4. EXAMPLE. Find a fundamental set of solutions of ( x-1) y 00-xy + y = 0 on the interval x > 1, given that y 1 ( x ) = e x is a solution. HOMEWORK: SECTION 3.4...
View Full Document